2018
DOI: 10.18535/jmscr/v6i12.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glucose 6-Phosphate Dehydrogenase Deficiency (G6PDd) and Haemoglobin Variants on Malaria in Port Harcourt, Rivers State, Nigeria

Abstract: The burden of the disease due to malaria is believed to share the same geographical distribution that correlates with G6PD deficiency and sickle cell haemoglobin (HbSS) due to protective advantage against malaria parasites. This study was aimed at studying the interactions between G6PD and haemoglobin variants in sub-clinical malaria infected pregnant women. Five millilitres (5ml) of venous blood was collected aseptically into 1% diamine tetraacetic acid bottle and carefully mixed for the analysis. G6PD activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This study in relation to gestational age, showed that the prevalence of maternal malaria was higher among women in their second trimester (38.1%) followed by those in their third trimester (16.0%). This finding disagrees with the previous studies in other malaria endemic areas of sub-Saharan, where the level of malaria among pregnant women was significantly higher in their first then second trimester of gestation (Katz et al, 2013) but it agrees with the findings of Kozuki, et al, (2013), which they conducted in Bandiagara, Mali; and Eastern Sudan were prevalence rate of malaria infection was higher among pregnant women in their second and third trimester establishing that immunosuppression during the second trimester of pregnancy, as a result the presence of high adrenal steroid levels, as well as chorionic gonadotrophin and fetoprotein in the blood, may lead to depression of the lymphocyte activity, which may be responsible for higher susceptibility of women in their second and third trimester of pregnancy to the malaria parasite, as recorded in the studies conducted by Oliver et al;(2014).…”
Section: Discussionmentioning
confidence: 90%
“…This study in relation to gestational age, showed that the prevalence of maternal malaria was higher among women in their second trimester (38.1%) followed by those in their third trimester (16.0%). This finding disagrees with the previous studies in other malaria endemic areas of sub-Saharan, where the level of malaria among pregnant women was significantly higher in their first then second trimester of gestation (Katz et al, 2013) but it agrees with the findings of Kozuki, et al, (2013), which they conducted in Bandiagara, Mali; and Eastern Sudan were prevalence rate of malaria infection was higher among pregnant women in their second and third trimester establishing that immunosuppression during the second trimester of pregnancy, as a result the presence of high adrenal steroid levels, as well as chorionic gonadotrophin and fetoprotein in the blood, may lead to depression of the lymphocyte activity, which may be responsible for higher susceptibility of women in their second and third trimester of pregnancy to the malaria parasite, as recorded in the studies conducted by Oliver et al;(2014).…”
Section: Discussionmentioning
confidence: 90%
“…Purposive sampling and randomized method were used in the selection of subjects, with due consideration of the total number of patients admitted in the clinic/ward in the University of Port Harcourt Teaching Hospital, Port Harcourt and the Federal Medical Centre, Yenagoa. The sample size was obtained using a prevalence of sickle cell anaemia of 2% [10] and the sample size was calculated using Cochran sample size formula [19]. By adding 10% of non-respondent, the sample size will be 33.…”
Section: Sample Sizementioning
confidence: 99%
“…However, worrying estimates indicate that the number of newborns with SCA will increase from approximately 300,000 in 2010 to 400,000 in 2050 [6][7]. The African continent, which has 3.6 million new cases of sickle cell trait (HbAS) and 238,000 SCA, remains the largest cradle of SCA genetic inheritance [8][9] with a 3% and 2% prevalence of HbSS in Rivers and Bayelsa States respectively, both in South-Southern Nigeria [10][11]. Nigeria, and the Democratic Republic of Congo would urgently need to plan policies for prevention and management of SCA, so that implementations carried out in 2015 could save many lives by 2050 [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to new data it may be responsible for up to 24% of total child death in sub-Saharan Africa [6]. The prevalence of malaria infection among children under five in Nigeria is 25% -30% causing over 300,000 death per year [7] and 61.2% pregnant women infected in Rivers state [8]. A retrospective study of children presenting with symptoms suggestive of malaria carried out in the University of Port Harcourt Teaching Hospital revealed a prevalence of 60.6%.…”
Section: Introductionmentioning
confidence: 99%